Improving group forecast accuracy via mindful organizing - Rosemberg Montes, Efrain (IE University, 2024)
In the last four decades, researchers have acknowledged that understanding the organizational aspects of forecasting could shed light on often-cited challenges in the field: improving prediction accuracy, implementing forecasting techniques, and achieving alignment between firms' functions. Despite this pledge, organizational dynamics in forecasting remain largely uncharted, possibly due to an over-emphasis on the functionalistic paradigm that posits forecasters aid decision-making by predicting a concrete reality "out there" that exists independently of the participants' interactions and beliefs. Within this context, this thesis proposes a paradigmatic step towards a functionalist-interpretive "transition zone" using the mindful organizing framework as a bridge (Weick, 1995; Weick et al., 1999). This framework conveys a nuanced template of real-life interactions focused on collective interpretive work and a particular sensitivity to analyze errors and near misses. While retaining the objective goal of accuracy, this work can contribute to the forecasting field from three angles: a) providing insights into team communication micro-processes that could debias judgment, b) emphasizing the role of error disclosure and deliberation in team performance, and c) substantiating theoretically the inherent subjectivity of the forecast process where participants interact actively to predict and decide. We report the empirical findings of an experimental study involving 40 hierarchical forecasting triads—one leader and two team members—to test the role of mindful organizing in judgmental forecasting. Compared to the control group, we find systematic improvements in point forecast accuracy when groups have received interventions to foster interactions aligned with the mindful organizing framework. However, mindful organizing in forecasting teams does not improve interval accuracy scores (MSIS). Analyzing the teams’ interactions via chat functionality sheds light on more extended and nuanced communication in the intervention groups, prompting participation and opposing views amongst team members. Implications for the theory and practice of forecasting in organizational environments are discussed.